PLGA nanoparticles for capsaicin delivery: enhanced encapsulation efficiency and pro-apoptotic activity in HEPG2 cells - Mulè, Chiara; Caputo, Tania Mariastella; Montefusco, Antonio; Romanelli, Antonio Massimiliano; Caputo, Ivana; Paolella, Gaetana; Aliberti, Anna; Cusano, Andrea (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCapsaicin (trans-8-methyl-N-vanillyl-6-nonenamide) (Cap) is a lipophilic alkaloid derived from Capsicum annuum. It was observed that Cap has an antitumoral activity in several cancer types, in particular in liver, colon and breast cancer. Actually, the use of Cap in the cancer therapy is limited by its very low bioavailability, a short half-life and side effects as mouth and stomach irritations and burning sensation. To overcome these limitations, the Cap has been encapsulated in carriers in order to reduce the adverse effect and to help the delivery in the cancer cells. In this study, we synthesized Poly(lactic co-glycolic acid) (PLGA) nanoparticles (NPs) to encapsulate Cap (PLGA-Cap), optimizing the synthetic strategy and improving its efficiency and safety. This is the first time that PLGA-Cap NPs was tested on HepG2 cells line for Hepatocellular carcinoma (HCC) therapy.MethodsNPs are characterized by Dynamic Light Scattering (DLS), Fourier transform infrared spectroscopy (FTIR), Morphological analysis by scanning transmission electron microscopy (STEM) and Reverse-Phase High Liquid Chromatography (RP-HPLC) to study their physicochemical properties and the best condition in terms of size, PDI and encapsulation efficiency. In vitro biological MTT assay was performed on HepG2 cells to observe the cell proliferation in response to PLGA-Cap. The apoptosis induced by Cap was evaluated the enzymatic activity of caspase 3, Bcl2 and Bax expression by Western blot and ROS activity.Results and DiscussionOur preparation showed the highest Encapsulation Efficiency (96%) reported by the literature, showing an improvement of 21% compared to what is actually reported. In vitro experiments revealed that PLGA-Cap formulation induced similar biological effects in terms of cell viability compared to free Cap. Moreover, HepG2 cancer cells treated with PLGA-Cap exhibited increased caspase 3 activity respect to those treated with free Cap.ConclusionIn conclusion we demonstrated that our preparation showed an improvement in encapsulation parameters and in pro-apoptotic and anticancer activity in HepG2 cells.